Penerapan Metode Simple Additive Weighting untuk Penentuan Distributor Terbaik di Apotek Yessa Farma - Sugiono, Agus; Himawan, Imam (Universitas Indraprasta PGRI, 2025)
AbstractThe problem faced is that the calculation is still done manually,may resulting errors in determining the selection of distributors based on the cheapest price, discounts given, payment terms and speed of product delivery, then there is no decision support system in the distributor determination process at Yessa Farma Pharmacy because it still uses a conventional system and not a computerized system. The purpose of designing a decision support system for selecting distributors is to make it easier for pharmacy owners to choose distributors and the calculation process is computerized using the SAW method. The method used in this study is Simple Additive Weighting in solving the problems that have been studied. The results obtained in this study are to produce an accurate report on the best distributor selection data at Yessa Farma Pharmacy so that it can help in making strategies in the future. The application system designed is suitable for use in the distributor selection process at Yessa Farma Pharmacy because it is in accordance with the needs, so it can facilitate the administration in the data input process and report generation. Keywords: SPK, Supplier, Pharmacy, SAW